Intraocular gases and climate change: a call for sustainable vitreoretinal surgery - Silva, Joseph Paolo Y.; Salongcay, Recivall P. (Frontiers in Public Health, 2025)
Perfluoropropane (C₃F₈) and sulfur hexafluoride (SF₆) are established agents in vitreoretinal surgery. Their tamponade properties support anatomic success, but both gases have very high global warming potentials and extremely long atmospheric lifetimes. Given the health sector’s considerable share of global greenhouse emissions, emissions attributable to intraocular gases constitute a discrete, measurable, and modifiable component of surgical practice. This Perspective synthesizes published evidence on the climate impact of C₃F₈ and SF₆ in routine vitreoretinal care and outlines actions at three levels. First, clinical practice: standardize low-concentration mixtures, match prepared volume to need, improve decanting technique, and consider air tamponade in appropriate indications. Second, implementation systems: training, checklists, and simple process metrics (prepared-to-injected ratios; concentration adherence) to reduce variation and waste. Third, institutional and policy measures: procurement criteria that favor lower GWP options and right sized packaging, guideline updates, audit indicators, and product level carbon disclosure. These steps do not introduce new clinical risk when applied with standard safeguards and may yield cost savings by reducing gas consumption. Because fluorinated intraocular gases are potent, long lived, and tied to modifiable routines, targeted measures in this niche can produce outsized gains for planetary health relative to effort.